KEANEKARAGAMANA JENIS SERANGGA TANAH DI HUTAN LINDUNG GUNUNG MAHAWU PROVISI SULAWESI UTARA - Ujiman Gay; Dr.Ir. Terry M. Frans MSi; Dr.Ir. Ventje V. Memah MP (Universitas Sam Ratulangi, 2018)
ABSTRACT Soil insects are insects whose part or whole life is in the soil. Soil insects are used as indicators to determine the stability of an ecosystem, so this study aims to see the effect of the diversity of soil types on forest strata. The Mahawu mountain protected forest is located in Tomohon, North Sulawesi Provinc. Forests with altitude of 800 m to 1372 m above sea level, with forest area of 40.44 hectares. The diversity of soil types of insects in protected forests of mahawu mountain is included in the medium category (1> H <3). The highest number of insect populations was found in the two-storey forest floor of Family Dermaptera = 34 heads, one-strata forest of Gryllidae Family amounted to 26 heads, and three-strata forest of Cerambycidae family amounted to 15 heads. Keywords : Soil insects.